One Kecamatan One Center for Entrepreneurship (OK-OCE) dalam Ekosistem Kewirausahaan Kota Jakarta: Kerangka Kebijakan dan Kemitraan Stakeholders - Bani Pamungkas (Jurnal Universitas Paramadina, 2017)
The OK-OCE program is recognized to have attracted the attention of the Jakarta public in the 2017 elections. The public catch thatthe ideas in line with the needs of the people who are drowning in the face of unfavorable economic conditions.After being inaugurated as Governor and Vice Governor of DKI Jakarta last October, the Anis-Sandi started to work on his political promises, including OK-OCE program. Through this research is reviewed how the idea of entrepreneurship that has attracted Jakarta public attention as a campaign promise, can be transformed into policy.